The role of pharmacists in the renal multidisciplinary team at a tertiary hospital in South Africa: Strategies to increase participation of pharmacists - Tebogo L. Manyama; Rendani M. Tshitake; Noko B. Moloto (AOSIS, 2020)
Background: Pharmacists are often marginalised from participating fully in a Multidisciplinary Team (MDT). Pharmacists can contribute in the renal MDT by minimising drug-related problems and optimising therapy. Aim: The study aimed to explore the current role of pharmacists in renal care at a tertiary hospital in South Africa, and to recommend strategies to improve their participation in the renal MDT. Method: An exploratory descriptive qualitative study was conducted using semi-structured interviews. The participants were selected using purposive sampling. The audiotaped interviews were transcribed exactly as spoken and analysed using thematic content analysis. Results: Three themes emerged from the analysis: pharmacist's current scope of practice within the renal MDT, potential future roles of pharmacists, and perceived barriers to participation of pharmacists within the renal MDT. Furthermore, participants provided recommendations to increase pharmacist's participation in the renal MDT: that is standardisation of practice, skills development of both pharmacist and pharmacist assistants and recognition of pharmacist services in the wards. Conclusion: The role of pharmacists at Pietersburg Hospital is the official name of the hospital is confined to stock management and dispensing. Efforts should be made to improve the participation of pharmacists in the MDTs with the intention to standardise the practice of pharmacists in the wards, equip both pharmacists and pharmacist assistants with the necessary skills and recognise pharmacist's services in the wards.